Ammonium removal from municipal wastewater through ion exchange - Low, Ching Wei (Nanyang Technological University, 2021)
Ammonium removal is an important aspect in municipal wastewater treatment. The objectives of this study were to evaluate on the ammonium removal efficiency through adsorption, with the adsorbent of synthetic zeolite (NaA), and modified biochar (MBC). The kinetics, isotherms, and effects of pH to ammonium removal of both NaA and MBC were investigated. Langmuir adsorption model provides a better description, compared to Freundlich, of the adsorption mechanism of both NaA and MBC and the maximum adsorption capacities were found to be 43.5 mg/g and 10.7 mg/g, respectively. Results indicated that influent pH has a significant influence over the removal of ammonium. The peak ammonium adsorption for NaA and MBC were found to occur at pH 6 and 9, respectively. Simulated ammonium removal treatment of municipal wastewater was carried out for MBC through column test and the removal efficiency was found to reach 61.4 % with EBCT of 25min.